Microsporum nanum relato do segundo caso de infecção humana no Brasil - Camargo, R. M. P. [UNESP]; Silva, N. A. S. [UNESP]; Marques, Silvio Alencar [UNESP]; Stolf, Hamilton Ometto [UNESP]; Dillon, N. L. [UNESP] (Instituto de Medicina Tropical, 1984)
É comunicado o segundo caso de infecção humana por Microsporum nanum no Brasil. A investigação epidemiológica visando determinar a fonte de infecção não obteve sucesso. O padrão dermatológico das lesões foi o de Tinea corporis clássica.

The second Brazilian case of human infection by Microsporum nanum is reported. The epidemiologic investigation to detect the origin of the infection was unsuccessful. The dermatologic pattern of the lesions was the classic Tinea corporis.
Report of the second human infection case by Microsporum nanum, in Brazil